Kinetic and energetic performances of thermometric material TiCo1-xMnxSb: modelling and experiment - Krayovskyy Volodymyr; Pashkevych Volodymyr; Rokomanyuk Mariya; Haranuk Petro; Romaka Volodymyr; Stadnyk Yuriy; Romaka Lyubov; Horyn Andriy (Lviv Politechnic Publishing House, 2021)
The results of a complex study of the semiconductor thermometric material TiCo1-xMnxSb, x=0.01–0.10, for the production of sensitive elements of thermoelectric and electro resistive sensors are presented. Microprobe analysis of the concentration of atoms on the surface of TiCo1-xMnxSb samples established their correspondence to the initial compositions of the charge, and X-ray phase analysis showed the absence of traces of extraneous phases on their diffractograms. The produced structural studies of the thermometric material TiCo1-xMnxSb allow to speak about the ordering of its crystal structure, and the substitution of Co atoms on Mn at the 4c position generate structural defects of acceptor nature. The obtained results testify to the homogeneity of the samples and their suitability for the study of electrokinetic performances and the manufacture of sensitive elements of thermocouples. Modeling of structural, electrokinetic, and energetic performances of TiCo1-xMnxSb, x=0.01–0.10, for different variants of the spatial arrangement of atoms is performed. To model energetic and kinetic performances, particularly the behavior of the Fermi level , the bandgap , the density of states (DOS) distribution was calculated for an ordered variant of the structure in which Co atoms at position 4c are replaced by Mn atoms. Substitution of Co atoms (3d74s2) by Mn (3d54s2) generates structural defects of acceptor nature in the TiCo1-xMnxSb semiconductor (the Mn atom contains fewer 3d- electrons than Co). This, at the lowest concentrations of impurity atoms Mn, leads to the movement of the Fermi level from the conduction band to the depth of the bandgap . In a semiconductor with the composition TiCo0.99Mn0.01Sb, the Fermi level is located in the middle of the bandgap , indicating its maximum compensation when the concentrations of ionized acceptors and donors are close. At higher concentrations of impurity Mn atoms, the number of generated acceptors will exceed the concentration of donors, and the concentration of free holes will exceed the concentration of electrons. Under these conditions, the Fermi level approach, and then the level of the valence band TiCo1-xMnxSb cross: the dielectric-metal conductivity transition take place. The presence of a high-temperature activation region on the temperature dependence of the resistivity ln(ρ(1/T)) TiCo1-xMnxSb at the lowest concentration of impurity atoms Mn, x=001, indicates the location of the Fermi level in the bandgap of the semiconductor thermopower coefficient α(T,x) at these temperatures specify its position - at a distance of ~ 6 meV from the level of the conduction band . In this case, electrons are the main carriers of current. The absence of a low temperature activation region on this dependence indicates the absence of the jumping mechanism conductivity. Negative values of the thermopower coefficient α(T,x) TiCo0,99Mn0,01Sb at all temperatures, when according to DOS calculations the concentrations of acceptors and donors are close, and the semiconductor is maximally compensated, can be explained by the higher concentration of uncontrolled donors. However, even at higher concentrations of impurity Mn atoms in TiCo0,98Mn0,02Sb, the sign of the thermopower coefficient α(T,x) remains negative, but the value of resistivity ρ(x, T) increases rapidly, and the Fermi level deepens into the forbidden zone at a distance of ~ 30 meV. The rapid increase in the values of the resistivity ρ(x, T) in the region of concentrations x=0.01–0.02 shows that acceptors are generated in the TiCo1-xMnxSb semiconductor when Co atoms are replaced by Mn, which capture free electrons, reducing their concentration. However, negative values of the thermopower coefficient α(T,x) are evidence that either the semiconductor has a significant concentration of donors, which is greater than the number of introduced acceptors (x=0.02), or the crystal simultaneously generates defects of acceptor and donor nature. The obtained result does not agree with the calculations of the electronic structure of the TiCo1-xMnxSb semiconductor. It is concluded that more complex structural changes occur in the semiconductor than the linear substitution of Co atoms by Mn, which simultaneously generate structural defects of acceptor and donor nature by different mechanisms, but the concentration of donors exceeds the concentration of generated acceptors. Based on a comprehensive study of the electronic structure, kinetic and energetic performances of the thermosensitive material TiCo1-xMnxSb, it is shown that the introduction of impurity Mn atoms into TiCoSb can simultaneously generate an acceptor zone (substitution of Co atoms for Mn) and donor zones and of different nature. The ratio of the concentrations of ionized acceptors and donors generated in TiCo1-xMnxSb will determine the position of the Fermi level and the mechanisms of electrical conductivity. However, this issue requires additional research, in particular structural and modeling of the electronic structure of a semiconductor solid solution under different conditions of entry into the structure of impurity Mn atoms. The investigated solid solution TiCo1-xMnxSb is a promising thermometric material. Key words: Electronic structure; Resistivity; Thermopower.